Grisel's syndrome: a rare complication of tonsillectomy - Sia, K.J.; Tang, I.P.; Kong, C.K.; Nasriah, A. (Cambridge University Press, 2012)
Objectives:To discuss the pathophysiology of atlanto-axial subluxation as a rare complication of tonsillectomy, and to discuss the important radiological findings for diagnosis and treatment planning.Case report:We report a case of post-tonsillectomy atlanto-axial subluxation, also known as Grisel's syndrome, in a child. On the third day after surgery, the boy presented with torticollis with no neurological deficit. Rotatory atlanto-axial subluxation was clearly shown in computed tomography scans of the neck. Cervical traction for one week successfully reduced the subluxation, with no long-term sequelae.Conclusion:Pre-existing cervical ligamentous laxity and post-operative infection are believed to be the main causes of Grisel's syndrome. Although it is rare, patients are advised to seek treatment early if any neck pain or fever persists. Early diagnosis is important for better treatment outcome. Initial conservative measures are advised before more invasive cervical traction is adopted.